Construction of IRES-incorporated pMG36e lactococcal vector and its segregational instability in Escherichia coli - Lim, Y. Y.; Ibrahim, Noor Hidayah; Mustapha, Nurul Asyifah (Veterinary Association of Malaysia, 2018)
The increasing demand of Lactococcus lactis (L. lactis) beyond application in food industry raises the need to develop lactococcal bicistronic vector with target gene expression in a eukaryotic system for vaccination purposes. Despite the importance of functional studies of the expression vector in eukaryotic system, the stable and efficient host for vector propagation should be tackled. Therefore, the objectives of this study were to construct a pMG36e lactococcal vector containing modified eukaryotic expression cassette, with internal ribosome entry site (IRES) inserted between CMV promoter and Poly A signal to allow transcription and translation of two proteins in a single cassette and, study its stability in Escherichia coli (E. coli) TOP 10 as a propagation host. IRES sequence was PCR-amplified from pRetroX-IRES-ZsGreen1 vector, digested with EcoRV and XhoI, and ligated into eukaryotic expression cassette from pcDNA 3.1 HisA plasmid/vector. Constructed vector was transformed into E. coli TOP 10 and the orientation of IRES fragment in the modified eukaryotic expression cassette was confirmed by DNA sequencing. The modified eukaryotic expression cassette was PCR-amplified from pcDNA3.1HisA/IRES before sub-cloning into lactococcal vector pMG36e and transformed into E. coli TOP 10. pMG36e harbouring modified eukaryotic expression cassette was successfully constructed and transformed into E. coli TOP 10. However, the segregational instability of constructed vector in E. coli Top10 host was detected, which may have been caused by production of single-stranded intermediates and high-molecular weight DNA due to rolling-cycle replication of the pMG36e vector.